Changes in texture, flavor, and protein digestion of low-salt chickpea surimi composite gel: Based on Kanto cooking model and peptidomics - Qianqian Zhang; Li Yuan; Yunfei Kong; Zhiyu Xiong; Yulong Bao; Ruichang Gao (Food Chemistry: X, 2025)
Plant and animal protein complex systems are increasingly utilized in the food industry, but thermal processing effects on their quality still require investigation. Therefore, this study investigated the effect of cooking (Kanto cooking model, 85 °C, 0–12 h) on the quality of chickpea surimi composite gel (50 % plant protein substitution). Multidimensional analyses (texture analyzer, scanning electron microscope, electronic nose, gas chromatography–mass spectrometry, and peptidomics) demonstrated that the composite gel maintained stable cooking properties, with richer flavor profiles (30 key volatile organic compounds (VOCs)) and active peptides. With the extension of cooking time, its gel strength decreased (33.33 %), while springiness and flavor diversity increased (P < 0.05). Its protein digestibility also decreased (5.07 %), accompanied by altered peptide composition (type, proportion, and quantity) in digestion products. The results are expected to provide a reference for the research, development, and reprocessing of plant protein substitute products.